Who gets the carrot and who gets the stick? Evidence of gender disparities in executive remuneration - Kulich, Clara; Trojanowski, Grzegorz; Ryan, Michelle K.; Alexander Haslam, S.; Renneboog, Luc D. R. (Strategic Management Journal, 2011)
Abstract This paper offers a new explanation of the gender pay gap in leadership positions by examining the relationship between managerial bonuses and company performance. Drawing on findings of gender studies, agency theory, and the leadership literature, we argue that the gender pay gap is a context‐specific phenomenon that results partly from the fact that company performance has a moderating impact on pay inequalities. Employing a matched sample of 192 female and male executive directors of U.K.‐listed firms, we corroborate the existence of the gender pay disparities in corporate boardrooms. In line with our theoretical predictions, we find that bonuses awarded to men are not only larger than those allocated to women, but also that managerial compensation of male executive directors is much more performance‐sensitive than that of female executives. The contribution of attributional and expectancy‐related dynamics to these patterns is highlighted in line with previous work on gender stereotypes and implicit leadership theories such as the romance of leadership. Gender differences in risk taking and confidence are also considered as potential explanations for the observed pay disparities. The implications of organizations' indifference to women's performance are examined in relation to issues surrounding the recognition and retention of female talent. Copyright © 2010 John Wiley & Sons, Ltd.